Data analytics and machine learning fundamentals LiveLessons - Barton, Robert (Pearson, 2019)
"In Data Analytics and Machine Learning Fundamentals LiveLessons, experienced CCIEs Robert Barton and Jerome Henry provide more than 7 1/2 hours of personal instruction exploring the principles of big data analytics, supervised learning, unsupervised learning, and neural networks. In addition to delving into the fundamental concepts, Barton and Henry address sample big data and machine learning use cases in different industries and present demos featuring the most common tools (such as Hadoop, TensorFlow, Matlab/Octave, R, and Python) in various fields used by data scientists and researchers. At the conclusion of this video course, you will be armed with knowledge and application skills required to become proficient in articulating big data analytics and machine learning principles and possibilities."--Resource description page
Title from title screen (viewed January 28, 2020)
Keywords: Machine learning; Neural networks (Computer science); Quantitative research; Mathematical statistics -- Data processing; Neural Networks, Computer; Apprentissage automatique; Réseaux neuronaux (Informatique); Recherche quantitative; Statistique mathématique; Informatique; Mathematical statistics; Data processing